Kappa-Opioid Receptor Signaling in the Striatum as a Potential Modulator of Dopamine Transmission in Cocaine Dependence - Trifilieff, Pierre; Martinez, Diana (Frontiers in Psychiatry, 2013)
Cocaine addiction is accompanied by a decrease in striatal dopamine signaling, measured as a decrease in dopamine D2 receptor binding as well as blunted dopamine release in the striatum. These alterations in dopamine transmission have clinical relevance, and have been shown to correlate with cocaine-seeking behavior and response to treatment for cocaine dependence. However, the mechanisms contributing to the hypodopaminergic state in cocaine addiction remain unknown. Here we review the Positron Emission Tomography (PET) imaging studies showing alterations in D2 receptor binding potential and dopamine transmission in cocaine abusers and their significance in cocaine-seeking behavior. Based on animal and human studies, we propose that the kappa receptor/dynorphin system, because of its impact on dopamine transmission and upregulation following cocaine exposure, could contribute to the hypodopaminergic state reported in cocaine addiction, and could thus be a relevant target for treatment development.